TOTAL DESCRIPTION OF ERITROSIT, HEMOGLOBIN CONTENT AND THE VALUE OF FISH HEMATOKRITES Oreochromis niloticus) WITH FOOD CONTAINED Bacillus sp - Dinar Mey Jasika H; Iesje Lukistyowati; Henni Syawal (Berkala Perikanan Terubuk, 2017)
This research was conducted in October 2015-June 2016 which was held at Marine Microbiology Laboratory, Parasitic and Fish Disease laboratory and Aquaculture Technology Laboratory Faculty of Fisheries and Marine University of Riau, Pekanbaru. This study aims to determine the effectiveness of giving Bacillus sp. Which is isolated from giant prawns (Macrobrachium rosenbergii de Man) and tiger prawns (Penaeus monodon) into the diet can improve the health oftilapia (Oreochromis niloticus) seen the total picture of erythrocytes, hemoglobin and hematocrit values. The method used by using Completely Randomized Design (RAL), ie in each treatment done probiotik Bacillus sp. From prawns and tiger prawns using 3 levels of treatment and 3 replications. This research uses application method by spraying probiotic Bacillus sp. On commercial feed. As probiotic treatments were used Bacillus sp. The best isolate of UG4 isolated from digestive tract of giant prawns. As for the isolates of the digestive tract of tiger shrimp used probiotics Bacillus sp. The best isolate is UWH9. The result of this research shows that P2 (UWH9) treatment is the best isolate from the digestive tract of tiger shrimp with total erosite value of 205 x 104 cell / mm3, hemoglobin level 5.05 g / dL, hematocrit value 30%, absolute weight growth Of 23.16 g, and a survival rate of 80%.